Cutaneous manifestation in children with HIV/AIDS - Seyed Naser Emadi (Journal of Pediatrics Review, 2014)
The most recent studies have explained almost 2.3 million children are affected with HIV up to the end of 2009. Sub-Saharan Africa is the main region affected by AIDS compare to other parts of the world. Despite providing competent healthcare services to prevent mother-to-child transmission as a main way of infection to a newborn, an estimated 370,000 children were newly infected to HIV in 2009. Skin disorders are common and may even be the first manifestation of HIV in children.The most common skin illnesses are classified in four categories; infectious, inflammatory, neoplastic, and drug related (Highly Active Antiretroviral Therapy). In addition, unusual anatomical sites, disseminated skin